Standarisasi Pasien dan Ruang Simulasi Meningkatkan Kepuasan Mahasiswa Kedokteran Universitas Mataram dalam Pelaksanaan Keterampilan Medik Kardiovaskuler - Syamsun, Arfi; Ansyori, Maz Isa (Faculty of Medicine Universitas Mataram, 2012)
Introduction: Cardiovascular diseases have high morbidity and mortality rates. Skills in administering diagnosis and treatment of the diseases is part of general physician competencies according to the Indonesian Doctors Competency Standards. The teaching of cardiovascular lab skills at the Medical Faculty of the University of Mataram has not optimally prepared standardized simulation rooms and patients. As a result, this complicates students’ clinical understanding in handling cardiovasdcular events at the hospitals and clinics with different facilities. The effectiveness of the standardization is measured from results of skill lab exams and students’ satisfaction scores. Objectives: To identify the difference in the satisfaction and skills lab scores of cardiovascular physical exam and electrocardiography (ECG) installation among students of simulation room and patient standardization groups as compared to non-standardization groups. Method: This cross sectional study involved 20 students of 5th semester of the Faculty of Medicine, Mataram University. Samples were taken randomly based on prior stratified lab skills scores. They comprised 2 treatment groups and 2 control groups as follows: group 1, simulation room and patient standardization for cardiovascular physical exam; group 2, simulation room and patient standardization for ECG examination; group 3, simulation room and patient non-standardization for cardiovascular physical exam; group 4, simulation room and patient non-standardization for ECG examination. The students then attended a Master Course, lab skills demonstration, and independent practices for 2 weeks. Satisfaction scores are measured by means of a questionnaire whose contents were validly tested, while lab skills exam scores are measured using a standard checklist issued by the Medical Faculty. Unpaired t-test is used to identify the differences in the students’ satisfaction scores and skill lab scores among the 2 groups. Study Findings: There are significant differences in the mean of students’ satisfaction scores in terms of simulation patients, lab skills room, and instructors for cardiovascular physical exam and ECG exam between the standardization and non-standardization groups. There was no significant difference in the mean of scores on communicative and eticomedicolegal competence, clinical skills competence and clinical reasoning competence on cardiovascular physical exam and ECG exam between standardization and nonstandardization groups. Conclusion: Standardization of simulation patients and rooms for cardiovascular physical exam and ECG exam significantly increases students’ satisfaction scores but does not significantly increases students’ lab skills scores. Keywords: standardization, simulation patients, simulation room, satisfaction scores, lab skills scores.